Characteristics of the Anthocyanin Biosensor for Detecting Freshness of Gourami Fish (Osphronemus Gouramy) - Putri, Pridata Gina; Ningtyas, Kurnia Rimadhanti; Deary Amethy Zahrotinufus; Syah, Fahrul; Agassi, Taufik (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Biosensors are a form of innovation that overcomes the quality assurance problem of fishery products by observing the level of product freshness through color changes on the Biosensor in real-time, along with changes in the pH of the product. This research aims to obtain the best formulation of a starch-based biosensor with the addition of red dragon fruit peel anthocyanin extract as a freshness sensor and to determine the characteristics of a starch-based biosensor with the addition of anthocyanin extract as a freshness sensor. The starches used in this research were potato starch (A), cassava starch (B), corn starch (C), wheat starch (D), and sago starch (E). The results of this research are that the wheat starch biosensor (D) is the treatment with the characteristic results that most meet the JIS, namely the thickness value produced by wheat starch is 0.115 mm, the tensile strength value is 1,580 Mpa, and the elongation value is 109.489%. For the color characteristics of the best Biosensor, wheat starch has an L* value of 26, a* value of 24, a b* value of 25.2, and a Hue value of 16° hue. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water